Spontaneous tumor lysis syndrome following liver biopsy: a case report and literature review - Mao, Wenchao; Jiang, Xiangyang; Wang, Minjia; Cai, Kailun; Hu, Weihang; Gong, Shijin; Zhao, Yuexi (Frontiers in Oncology, 2025)
BackgroundTumor lysis syndrome (TLS), characterized by electrolyte imbalances and acute kidney injury, predominantly occurs following cytotoxic chemotherapy in hematologic malignancies. Spontaneous TLS (STLS) in solid tumors remains rare. This report describes STLS induced by a diagnostic liver biopsy and reviews the literature on procedure-associated TLS.Case presentationAn 84-year-old male presented with extensive hepatic metastases and markedly elevated tumor markers. Ultrasound-guided percutaneous liver biopsy confirmed the diagnosis of metastatic adenocarcinoma. Within 24 hours post-procedure, the patient developed acute respiratory failure, anuria, severe metabolic acidosis (pH 7.23), hyperkalemia (5.5 mmol/L), acute kidney injury (creatinine 299 μmol/L), hyperuricemia (716 μmol/L), and elevated lactate dehydrogenase (3953 U/L), fulfilling the diagnostic criteria for TLS. Concurrent hemothorax occurred. Continuous renal replacement therapy (CRRT) achieved rapid correction of metabolic derangements, with parameters returning to normal within seven days.ConclusionDiagnostic liver biopsy can induce STLS in patients with high-burden solid tumors. Our systematic analysis reveals that minimally invasive procedures may precipitate TLS, emphasizing the importance of prophylactic measures, early recognition, and immediate CRRT initiation for optimal outcomes.